Nutritional status mediates the relationship between sarcopenia and cognitive impairment: findings from the WCHAT study - Hu, Fengjuan; Liu, Hu; Liu, Xiaolei; Jia, Shuli; Zhao, Wanyu; Zhou, Lixing; Zhao, Yunli; Hou, Lisha; Xia, Xin; Dong, Birong (Aging Clinical and Experimental Research, 2021)
Background Sarcopenia is associated with cognitive impairment in older adults. However, the underlying mechanisms are not fully understood. Aim To explore the mediating role of nutritional status in the relationship between sarcopenia and cognitive impairment. Methods Three thousand eight hundred and ten participants (mean age 61.94 ± 8.01 years) from the West China Health and Aging Trend (WCHAT) study were included. We defined sarcopenia using the Asian Working Group for Sarcopenia (AWGS) 2019 criteria. Cognitive status and nutritional status were measured using the Short Portable Mental Status Questionnaire (SPMSQ) and the Mini Nutritional Assessment Short Form (MNA-SF). Relationships between sarcopenia, nutritional status, and cognitive function were explored using multiple linear regression. Two mediation models were generated to examine whether nutritional status mediates the association between sarcopenia and cognitive function using PROCESS macro version 3.5. Results The study involved 3147 (82.6%) non-sarcopenic, 387 (10.2%) sarcopenic, and 276 (7.2%) severely sarcopenic individuals. In mediation model 1, sarcopenia ( β = 0.208, 95% CI 0.072 to 0.344, P = 0.0028) was significantly associated with cognitive impairment, and nutritional status mediated this association (indirect effect = 0.162, bootstrap 95% CI 0.116 to 0.212). Mediation model 2 indicated that nutritional status exhibited a full mediating effect regarding the association between sarcopenia and cognitive impairment (indirect effect = 0.131, bootstrap 95% CI: 0.08 to 0.188; direct effect = 0.046, bootstrap 95% CI − 0.115 to 0.21) and a partial mediating effect regarding the association between severe sarcopenia and cognitive impairment (indirect effect = 0.21, bootstrap 95% CI: 0.143 to 0.283; direct effect = 0.476, bootstrap 95% CI: 0.234–0.724). Conclusions The relationship between sarcopenia and cognitive impairment was significantly mediated by nutritional status. Early nutritional interventions may prevent cognitive decline in sarcopenic older adults.